2022
DOI: 10.3389/fpsyg.2022.926375
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of personal values between COVID-19-related posttraumatic growth and life satisfaction among Chinese college students: A two-wave longitudinal study

Abstract: Despite considerable disruption of social order caused by the COVID-19 pandemic, it has also been said to contribute to positive psychological changes and influence on the perception of public life satisfaction. The present study aimed to explore the association between the COVID-19 related posttraumatic growth and life satisfaction and the mediating role of personal values. A two-wave longitudinal design was used. 226 self-quarantined Chinese college students (58.8% male) completed post traumatic growth inven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…With regards to COVID-19, a similar pattern of differential relationship between two types of event-related rumination and adaptational outcomes also emerged ( Cui et al, 2021 ; Hyun et al, 2021 ; Ikizer et al, 2021 ; Kang and Kim, 2021 ; Zeng et al, 2021 ; Wall et al, 2022 ; Xie et al, 2022 ). Overall, these studies indicate that the extent to which individuals engage in IR and/or DR could explain individual differences in adaptation during a pandemic, as in other cases of adversity.…”
Section: Introductionmentioning
confidence: 70%
“…With regards to COVID-19, a similar pattern of differential relationship between two types of event-related rumination and adaptational outcomes also emerged ( Cui et al, 2021 ; Hyun et al, 2021 ; Ikizer et al, 2021 ; Kang and Kim, 2021 ; Zeng et al, 2021 ; Wall et al, 2022 ; Xie et al, 2022 ). Overall, these studies indicate that the extent to which individuals engage in IR and/or DR could explain individual differences in adaptation during a pandemic, as in other cases of adversity.…”
Section: Introductionmentioning
confidence: 70%
“…Also, in Northfield and Johnston’s study [ 55 ], although ethnicity was not a significant predictor of PTG, a group difference was evident between African American and Caucasian participants, with African American participants reporting higher levels. Considering age and sex/gender, no significant differences in relation to PTG were reported in some studies investigating these variables [ 37 , 40 , 46 , 49 , 50 , 59 , 62 , 63 ]. In contrast, in the study by Celdrán et al [ 38 ] and Fino et al [ 42 ], women reported higher levels of growth, but of all the sociodemographic variables considered in the study by Celdrán et al [ 38 ], only younger age significantly correlated with higher PTG, and the same was found in the study by Northfield and Johnston [ 55 ]; by contrast, in the study by Na et al [ 54 ], being female was associated with pandemic growth.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding other personality traits, the study by Casali et al [ 37 ] revealed that out of the six character-related virtues (wisdom and knowledge, courage, humanity justice, temperance, and transcendence), only humanity was significantly associated with PTG. Optimism and self-compassion [ 39 ], self-transcendence [ 63 ], agreeableness [ 54 , 62 ], self-esteem [ 64 ], and sense of coherence [ 50 ] were also associated with higher levels of PTG. Other personality traits associated with PTG were extraversion, conscientiousness, and emotional stability [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this manner, the endurance of personal suffering would be made possible via dedication to these three domains beyond the self (Wong et al, 2021). Empirical study has affirmed that self-transcendent values and experiences bear positive associations with diminished depressive symptoms, improved emotional wellbeing, and post-traumatic growth (Bojanowska & Kaczmarek, 2018;Monroy & Keltner, 2022;Xie et al, 2022).…”
Section: Transcending the Self To Transcend Sufferingmentioning
confidence: 99%